A new ornithopod (Dinosauria; Ornithischia) from Antarctica - Coria, Rodolfo Anibal; Moly, Juan J.; Reguero, Marcelo Alfredo; Santillana, Sergio; Marenssi, Sergio Alfredo (Cretaceous Research)
A new ornithopod dinosaur from Antarctica, Trinisaura santamartaensis n. gen. et n. sp. is diagnosed by a unique combination of characters that includes a scapula with a spike-like acromial process with a strong and sharp lateral crest and longer than other ornithopods, a humerus with a rudimentary deltopectoral crest represented as a thickening on the anterolateral margin of the humerus, and shaft strongly bowed laterally, and an ischium gently curved along its entire length. The holotype specimen comprises vertebral and appendicular elements. The presence of axially elongate distal caudal vertebrae, pubis with long prepubic and postpubic processes, as well as a femur with a distinct anterior trochanter, pendant 4th trochanter and shallow anterior intercondylar groove constitute a combination of characters present in the Late Cretaceous Patagonian Gasparinisaura, Anabisetia and Talenkahuen. The materials were found on the surface enclosed in a hard sandstone concretion collected near the Santa Marta Cove, James Ross Island, from the lower levels of the Snow Hill Island Formation (Campanian). This is the first ornithopod taxon identified from this unit, and the second ornithischian dinosaur, after the ankylosaur Antarctopelta oliveroi. However, other ornithopod reports from nearby localities of James Ross and Vega islands in outcrops of the overlying Lopez de Bertodano Formation suggest that this clade was widely represented in the Campanian and Maastrichtian of the James Ross Basin, Antarctic continent. Fil: Coria, Rodolfo Anibal. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Universidad Nacional de Río Negro; Argentina Fil: Moly, Juan J. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias ...